Metagenomic insights into the relationship between gut microbiota and residual feed intake of small-sized meat ducks - Bai, Hao; Shi, Lei; Guo, Qixin; Jiang, Yong; Li, Xiaofan; Geng, Dandan; Wang, Chenxiao; Bi, Yulin; Wang, Zhixiu; Chen, Guohong; Xue, Fuguang; Chang, Guobin (Frontiers in Microbiology, 2023)
Introduction The objective of this study was to determine the regulatory effects of gut microbiota on the feed efficiency (FE) of small-sized meat ducks by evaluating correlations between gut microbiota and residual feed intake (RFI). Methods A total of 500 21-day-old healthy male ducks with similar initial body weights (645 ± 15.0 g) were raised contemporaneously in the same experimental facility until slaughter at 56 days of age. In total, nine low-RFI (LR) and nine high-RFI (HR) birds were selected for further gut microbiota composition and functional analyses based on the production performance, and the RFI was calculated from 22 to 56 days of age. Results Growth performance results indicated a significantly lower RFI, feed conversion ratio, feed intake, and average daily feed intake in the LR ducks (P < 0.05). Taxonomy results of gut microbiota showed the identification of 19 kinds of phyla and more than 250 kinds of genera in all samples. No significant discrepancies in cecal bacterial α-diversity were discovered between the LR and HR groups, which indicated that the microbial modulatory effects on RFI may be attributed to the bacterial composition, rather than the species diversity. Differential analysis of bacterial communities between the LR and HR groups showed a significant increment of Firmicutes and a significant decline of Bacteroidetes in the LR group (P < 0.05). Specifically, genera of Erysipelatoclostridium, Parasutterella, Fournierella, and Lactococcus significantly proliferated, while Bacteroides significantly decreased in the LR group (P < 0.05). Furthermore, correlation analysis showed that the RFI was significantly correlated with carbohydrate metabolism-related bacteria including Bacteroides, Alistipes, Bifidobacterium, Ruminiclostridium_9, Sellimonas, Oscillibacter, Escherichia-Shigella, Lactococcus, and Streptococcus. Conclusion In conclusion, the communities related to carbohydrate metabolism had positive regulatory effects on the FE of small-sized meat ducks, promoting it by improving the relative abundance and utilization of these communities. The present study provides valuable insight into the dynamics of gut microbiota underlying the variations in the FE of small-sized meat ducks.